JISMONIY TARBIYA DARSLARIDA MILLIY HARAKATLI O ‘YINLARNING O‘RNI - Qaljanov, P. (SCIENCE and SOCIETY, 2023)
The article provides information about the development of physical education, the role of physical education, national action games, and measures implemented in the field of physical education and sports today.